2017
DOI: 10.1016/j.watres.2016.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature thermal pre-treatment of municipal wastewater sludge: Process optimization and effects on solubilization and anaerobic degradation

Abstract: , Ray, M.B., Low-temperature thermal pre-treatment of municipal wastewater sludge: Process optimization and effects on solubilization and anaerobic degradation, Water Research (2017Research ( ), doi: 10.1016Research ( /j.watres.2016 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(42 citation statements)
references
References 35 publications
3
38
0
1
Order By: Relevance
“…However, in other cases, higher COD solubilization did not result in a higher biogas production, but sometimes in the same or even lower biogas production (Dhar et al, 2012;Haug et al, 1978;D.-H. Kim et al, 2013;J. Kim et al, 2013b;Nazari et al, 2016;Sapkaite et al, 2017). Since COD solubilization is apparently not an accurate parameter to predict the effectiveness of subsequent biogas production (Sapkaite et al, 2017), until now, batch or (semi)continuous, anaerobic digestion methods are the only useful and accurate tools to assess the effect of pre-treatments on the anaerobic biodegradability of WAS.…”
Section: Anaerobic Biodegradability and Biodegradationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in other cases, higher COD solubilization did not result in a higher biogas production, but sometimes in the same or even lower biogas production (Dhar et al, 2012;Haug et al, 1978;D.-H. Kim et al, 2013;J. Kim et al, 2013b;Nazari et al, 2016;Sapkaite et al, 2017). Since COD solubilization is apparently not an accurate parameter to predict the effectiveness of subsequent biogas production (Sapkaite et al, 2017), until now, batch or (semi)continuous, anaerobic digestion methods are the only useful and accurate tools to assess the effect of pre-treatments on the anaerobic biodegradability of WAS.…”
Section: Anaerobic Biodegradability and Biodegradationmentioning
confidence: 99%
“…The operational parameters are temperature and application time. Its main effect is the disintegration of cell membranes and a concomitant solubilization of organic compounds (Nazari et al, 2016).…”
Section: Process Description and Mode Of Actionmentioning
confidence: 99%
“…3 Various pretreatment processes, such as thermal treatment, biological treatment, chemical treatment, ultrasonic treatment, microwave treatment, and combinative treatment, such as chemo-sonic treatment, thermo-sonic treatment, and thermo-chemo-sonic treatment, are available. 4,5 Among them, biological pretreatment has quite a few benefits, which include minimum energy input, an eco-friendly process without pollution, and less harsh working conditions. 6 In addition, the complex high molecular weight and nexus interlace of extracellular polymeric substances (EPSs) protect the sludge from unfavorable conditions.…”
Section: Introductionmentioning
confidence: 99%
“…generally Nazari et al (2017). investigated the relationship between the degree of solubilization and biodegradability of wastewater sludge in AD due to low-The results showed that MSW was successfully processed after carrying out a feedstock pretreatment.…”
mentioning
confidence: 99%